Evaluasi Pengobatan pada Pasien Penyakit Paru Obstruksi Kronis (PPOK) di RST Dr. Asmir Salatiga: Evaluation of Treatment in Patients with Chronic Obstructive Pulmonary Disease at RST Dr. Asmir Salatiga - Jatmiko Rahmat; Dian Oktianti (Journal of Holistics and Health Sciences (JHHS), 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a lung condition characterized by a lack of airflow that can cause progressive and permanent damage to the lungs. This will cause symptoms of shortness of breath, coughing, wheezing and phlegm production. Patients with COPD require long-term therapy, so the accuracy of dosing must always be considered so that the therapeutic effect is achieved. The aim of this study was to determine the description of drug use and the accuracy of drug doses given to COPD patients. The method of this research is observational research presented descriptively with a retrospective approach using medical records of COPD patients RST dr. Asmir Salatiga for the period January - March 2023. A total of 65 samples were selected purposively. The data is analyzed and presented in the form of a percentage table. The accuracy of the dose was analyzed using the Drug Information Handbook edition 24. Based on the results of the study, it was possible to see the picture of combination therapy with long-acting corticosteroids and bronchodilators (Budesonide and Formoterol fumarate) as much as 73.8%, Xanthine (Aminophylline) as much as 46.2%, β-2 agonist (Salbutamol) as much as 29.2%, and Mucolytic (N-acetylcysteine) as much as (50.4%). There were 47 patients (72.3%) who received the correct dose according to the literature and 18 patients (27.7%) received the low dose. Conclusion: The most commonly used combination of drugs is corticosteroids and long-acting bronchodilators (Budesonide and Formoterol fumarate) 73.8%. Evaluation of the accuracy of COPD drug doses, 47 patients (72.3%) received doses that were in accordance with the literature.   ABSTRAK Penyakit Paru Obstruktif Kronik (PPOK) adalah kondisi paru-paru yang ditandai oleh kurangnya aliran udara yang dapat menyebabkan kerusakan progresif pada dan permanen pada paru-paru. Hal ini akan menyebabkan gejala sesak napas, batuk, mengi dan produksi dahak. Pasien dengan PPOK memerlukan terapi jangka panjang, sehingga ketepatan pemberian dosis harus selalu diperhatikan agar efek terapi tercapai. Tujuan penelitian ini adalah untuk mengetahui gambaran penggunaan obat, dan ketepatan dosis obat yang diberikan kepada pasien PPOK. Metode penelitian ini adalah penelitian observasional disajikan secara deskriptif dengan pendekatan retrospektif menggunakan catatan rekam medik pasien PPOK RST dr. Asmir Salatiga periode Januari - Maret 2023. Sebanyak 65 sampel yang dipilih secara  purposive. Data dianalisis dan disajikan dalam bentuk tabel persentase. Ketepatan dosis dianalisa menggunakan panduan Drug Information Handbook edisi 24. Berdasarkan hasil penelitian dapat diketahui gambaran terapi kombinasi kortikosteroid dan bronkodilator kerja lama (Budesonide dan Formoterol fumarate) sebanyak 73,8%, Xantin (Aminofilin) sebanyak 46,2%, Agonis β-2 (Salbutamol) sebanyak 29,2%, dan Mukolitik (N-asetilsistein) sebanyak (50,4%). Terdapat 47 pasien (72,3%)  mendapatkan dosis yang tepat sesuai literatur dan 18 pasien (27,7%) mendapatkan dosis rendah. Simpulan: Kombinasi obat paling banyak digunakan golongan kortikosteroid dan bronkodilator kerja lama (Budesonide dan Formoterol fumarate) 73,8%. Evaluasi ketepatan dosis obat PPOK, 47 pasien (72,3%) mendapatkan dosis yang sesuai dengan literatur.